2012
DOI: 10.1111/j.1445-2197.2012.06083.x
|View full text |Cite
|
Sign up to set email alerts
|

Tourniquet application only during cement fixation in total knee arthroplasty: a double‐blind, randomized controlled trial

Abstract: Restricting tourniquet application to the period of cementing is associated with a significantly higher risk of transfusion. This approach is impractical if it is not offset by gains in functional recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
49
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 29 publications
(53 reference statements)
1
49
0
Order By: Relevance
“…A study with a mean of 60 minutes provides more predictable data. The randomized studies we cited in our manuscript with a mean tourniquet time beyond 60 minutes have greater blood loss than our study and Kvedaras et al For example, Mittal et al [8] had a mean 1536 mL blood loss with a tourniquet time of mean 76.4 minutes.…”
mentioning
confidence: 38%
See 2 more Smart Citations
“…A study with a mean of 60 minutes provides more predictable data. The randomized studies we cited in our manuscript with a mean tourniquet time beyond 60 minutes have greater blood loss than our study and Kvedaras et al For example, Mittal et al [8] had a mean 1536 mL blood loss with a tourniquet time of mean 76.4 minutes.…”
mentioning
confidence: 38%
“…Two studies [5,8] comparing operative tourniquet use with cementation tourniquet were published in parallel with ours. Therefore, we did not discover them with our literature search.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Although the authors mentioned that there were no previous studies comparing the effects of tourniquet used only during cementing, we found two studies on the same topic published before the current study [4,7]. Kvederas and colleagues [4] compared three groups undergoing TKA in a Level II study.…”
mentioning
confidence: 83%
“…The second study by Mittal and colleagues [7] noted higher transfusion rates with the short tourniquet group (cementation tourniquet). The authors had to abandon the study due to unacceptably high transfusion rates in the cementation-only tourniquet group.…”
mentioning
confidence: 96%